EVALUASI KINERJA DAN KEMAMPUAN KEUANGAN DAERAH KOTA MAGELANG - Shania Nur Chasanah; Jihad Lukis Panjawa (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2020)
This study aims to analyze the performance and financial capability of Magelang City in the period 2014 - 2018. This study uses a quantitative approach with secondary data. The analytical tool used to measure the financial performance of the City of Magelang is a ratio and to calculate the financial capacity of the region measured by the index Share, Growth, Elasticity. The results showed the city of Magelang entered the category of low. The level of regional financial dependency shows a very high level of dependency. The degree of fiscal decentralization is in the moderate category. The level of effectiveness of regional income is very effective. The results of the calculation of the regional financial performance index (IKK) show that financial capacity is relatively high. Other findings from the mapping of regional financial capacity based on the quadrant method, the position of the city of Magelang is in quadrant III. This condition is also not ideal. The big role of PAD in Total Spending has a small chance because the growth of PAD is small. The contribution of PAD to total expenditure is high, but the growth of PAD is low. Efforts to further increase PAD by optimizing resource management and expanding the potential of the economic sector.